Answer:
7 1/2
Before simplification: 15/2
Step-by-step explanation:
Answer:
The equation of the function: y = mx + b
- m = slope = (y₂ - y₁)/(x₂ - x₁) = [5 - (-3)]/(4 - 0) = (5 + 3)/4 = 8/4 = 2
- b = y-intercept = -3
Therefore, the equation is <u>f(x) = 2x - 3</u>
When x = 0, f(x) = 2(0) - 3 = <u>-3</u>
When x increases by 1, f(x) increases by <u>2</u> (slope = the rate of change)
Answer:
y=5x+8.50
Step-by-step explanation:
Answer:
1+1=a a=solution
Step-by-step explanation:
10x= -8x + 36
-8x -8x
———————-
2x= 36
— —
2 2
X=18